Microwave-assisted V2O5 nanoflowers for efficient lithium-ion battery. (2nd January 2023) - Karthik, K.; Pradeeswari, K.; Mohan Kumar, R.; Murugesan, R.
ABSTRACT: A facile approach to synthesise V2 O5 nanoflowers are adopted through the microwave-assisted method. The as-prepared V2 O5 was characterised by the X-ray diffraction, scanning electron microscopy analyses. The X-ray diffraction spectra confirmed the formation of the orthorhombic crystal structure of V2 O5 nanoflowers with an average crystallite size of 20 nm. FTIR results showed the V-O-V stretching mode vibration at 442 cm −1 . The above material has studied as cathode material for lithium-ion batteries (LIB) at C/10 rate and the results showed, V2 O5 nanoflowers delivered the specific capacity of 241 mAh g −1 than the commercial V2 O5 of 98 mAh g −1 at 1.5–4.0 V apart from this, better cycle stability over 100 charge-discharge cycles and reasonable discharge capacities obtained at high C-rates. These results suggest enhancement of LIB capacity due to high surface area and good porosity of mesoporous V2 O5 nanoflowers.